From Foreigner Pedagogy to Intercultural Education: An analysis of the German responses to diversity and its impacts on schools and students - Faas, Daniel (My University, 2008)
Germany has been reluctant to adapt its education systems to the growing number of minority ethnic students, and politicians and policy makers have only recently officially acknowledged that Germany is an immigration country despite decades of mass immigration. This article first provides a socio-historical analysis of the German responses to migration-related cultural and religious diversity by tracing the development of educational policies from assimilationist notions of `foreigner pedagogy? in the 1960s and 1970s to intercultural education, which slowly emerged in schools in the 1980s and 1990s. However, unlike European education, intercultural education still lacks official support in some German federal states. Drawing upon qualitative data collected in two Stuttgart secondary schools, the article then discusses the ways in which schools and students have mediated such macro-level policies. Goethe Gymnasium (a university-track school) promoted European values alongside multicultural values whereas Tannberg Hauptschule (a vocational-track school) was close to being Eurocentric and positioned minority ethnic students as the `Other?. The findings suggest that Germany still has some way to go to overcome cultural insensitivities, to increase minority ethnic representation amongst teachers and to promote both diversity and civic cohesion.
PUBLISHED
Keywords: Intercultural education; Cultural diversity; Secondary schools; Assimilation; Identities in Transformation; Inclusive Society; International Integration